Periodic words connected with the Fibonacci words - Barabash, G.M.; Kholyavka, Ya.M.; Tytar, I.V. (Carpathian Mathematical Publications, 2016)
In this paper we introduce two families of periodic words (FLP-words of type 1 and FLP-words of type 2) that are connected with the Fibonacci words and investigated their properties.